Deteksi Ektoparasit Vorticella sp. pada Udang Vaname (Litopenaeus vannamei) di Desa Akar-Akar Kecamatan Bayan Kabupaten Lombok Utara - Gusti Ayu Riskha Sutrisno; Candra Dwi Atma; Iwan Doddy Dharmawibawa; Ni Luh Lasmi Purwanti (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to detect the presence of ectoparasites Vorticella sp. in whiteleg shrimp and its correlation with the quality of the cultivation environment in Akar-Akar Village, Bayan District, North Lombok Regency. The research method used was microscopic examination by making preparations from tissues consisting of carapace, walking legs, swimming legs, and tail. The total population was 12,000 individuals with a required sample size of 100 individuals. Furthermore, the data obtained were analyzed descriptively. The results showed that out of 100 samples, all were positive for Vorticella sp. and the prevalence value was 100%. Water quality showed a temperature of 32oC, total ammonia 0.072 mg/L, and orthophosphate 2.110 mg/L. More extreme conditions were found at DO levels reaching 0 mg/L. Meanwhile, salinity levels at 24.7 ppt, pH 7.18, and nitrite 0.049 mg/L were still within the normal range. The conclusion of this study was that all shrimp were detected with Vorticella sp., which is suspected to be closely related to poor water quality.